Identifikasi Dan Pemetaan Morfometri Daerah Aliran Sungai Martapura Menggunakan Teknologi GIS - Sobatnu, Ferry; Irawan, Faris Ade; Salim, Agus (Jurnal Teknik Sipil, 2017)
The low location of the Banjar district land from the sea surface causes the flow of water on the soil surface becomes substandard. Consequently some areas always stagnant to reach 29.93 %, some 0.58 % flooded periodically. Almost every year when the rainy season arrives with a high intensity in the Martapura area there is a flood with an altitude of up to Â± 1 meter. Based on data of regional disaster management agency (BPBD), there are eight districts that are prone to flooding. Namely, Sungai Pinang district, Sambung Makmur, Pengaron, Astambul, Karang Intan, Martapura, Sungai Tabuk, dan Mataraman. Research was conducted with the help of Arcgis software using a calculate geometry tool to identify morphometry. Watershed morphometry is a quantitative measure of watershed characteristics associated with the geomorphological aspects of a region. These characteristics are related to the rainwater drainage process that falls within the watershed. The research results show watershed Martapura has an area of 453.88 km2, the length of the main river reaches 36,566 meters, the slope (gradient) of 0.022 %. River density level is 0.828 km/km2.The order level of the river reaches 10 level. The pattern of the river is rektangular with the type of watershed in parallel. Based on data mapping and identification of Martapura river basin, so that important. information can be generated. such morphometric data can be used as reference for environmental problem solving and watershed management.